Spinal cord injury increases the reactivity of rat tail artery to angiotensin II - Al Dera, Hussain; Brock, James A. (Frontiers in Neuroscience, 2015)
Studies in individuals with spinal cord injury (SCI) suggest the vasculature is hyperreactive to angiotensin II (Ang II). In the present study, the effects of SCI on the reactivity of the rat tail and mesenteric arteries to Ang II have been investigated. In addition, the effects of SCI on the facilitatory action of Ang II on nerve-evoked contractions of these vessels were determined. Isometric contractions of artery segments from T11 (tail artery) or T4 (mesenteric arteries) spinal cord-transected rats and sham-operated rats were compared 6-7 weeks postoperatively. In both tail and mesenteric arteries, SCI increased nerve-evoked contractions. In tail arteries, SCI also greatly increased Ang II-evoked contractions and the facilitatory effect of Ang II on nerve-evoked contractions. By contrast, SCI did not detectably change the responses of mesenteric arteries to Ang II. These findings provide the first direct evidence that SCI increases the reactivity of arterial vessels to Ang II. In addition, in tail artery, the findings indicate that Ang II may contribute to modifying their responses following SCI.